Defending and Defining the Faith: An Introduction to Early Christian Apologetic Literature - Williams, D. H. (Oxford University Press, 2020)
Christian apologetics in the patristic era should be understood broadly as a defense of Christian beliefs and practices against non-Christian beliefs, practices, and policies (religious, social, and political) that were either antithetical to Christian beliefs and practices or openly hostile to Christianity. The advantage of this conceptualization of apologetics is that it enables readers to follow the discussion of Christian responses to Hellenistic culture beyond the context of persecution associated with the pre-Constantinian period, which tends to be where many scholarly projects on apologetics end. The reader is also invited to see the links in the intellectual trajectory from early second-century apologetics through those written in the early fifth century, prompting deeper reflection about the process of Christian self-definition in late antiquity. This book explores Christian apologetic literature from the second through fifth centuries, examining the writers within the intellectual context of their times. The book argues that most apologies were not directed at a pagan readership. In most cases, ancient apologetics had a double object: to instruct the Christian, and persuade less devout Christians or non-Christians who were sympathetic to Christian claims. Taken cumulatively, it finds that apologetic literature was integral to the formation of Christian identity in the Roman world.
paid